Essays on secularism and multiculturalism - Modood, Tariq (Rowman & Littlefield International, 2019)
Introduction : rethinking political secularism : the multiculturalist challenge -- The racialisation of Muslims/Muslims as "race relations"actors -- Racism, culturalism and cultural racism -- Ethno-religious assertiveness out of racial equality -- Maintaining civility and the feelings of the hated -- Islamophobia and the struggle for recognition -- Pointing to a multicultural future : rethinking race, ethnicity, religion and britishness -- Multiculturalism and secularism -- Muslims, religious equality and secularism -- Multicultural citizenship and the Shari'a controversy in Britain -- Moderate secularism, religion as identity and respect for religion -- Multiculturalism and the "crisis of secularism" -- State-religion connexions and multicultural citizenship -- Multiculturalizing secularism -- Intercultural public intellectual engagement.